2022
DOI: 10.3389/fmicb.2022.975365
|View full text |Cite|
|
Sign up to set email alerts
|

Genotype–phenotype correlations within the Geodermatophilaceae

Abstract: The integration of genomic information into microbial systematics along with physiological and chemotaxonomic parameters provides for a reliable classification of prokaryotes. In silico analysis of chemotaxonomic traits is now being introduced to replace characteristics traditionally determined in the laboratory with the dual goal of both increasing the speed of the description of taxa and the accuracy and consistency of taxonomic reports. Genomics has already successfully been applied in the taxonomic rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…The colonies exhibited a pink-orange hue on GYM Streptomyces , showcasing irregularities with a dry surface. A diffusible pink pigment was observed on medium 5322 (ISP7), while a distinctive brown pigment was observed on medium 5006, a characteristic not reported for other Blastococcus type strains [2–10] (Fig. S1A, available in the online version of this article).…”
Section: Cultural Morphological and Physiological Characterizationmentioning
confidence: 77%
See 1 more Smart Citation
“…The colonies exhibited a pink-orange hue on GYM Streptomyces , showcasing irregularities with a dry surface. A diffusible pink pigment was observed on medium 5322 (ISP7), while a distinctive brown pigment was observed on medium 5006, a characteristic not reported for other Blastococcus type strains [2–10] (Fig. S1A, available in the online version of this article).…”
Section: Cultural Morphological and Physiological Characterizationmentioning
confidence: 77%
“…The genus Blastococcus [1] encompasses 15 species with validly published names sourced from diverse environments. Blastococcus species have been identified in habitats as varied as the seawater of the Baltic Sea ( Blastococcus aggregatus [1]), monument samples (including Blastococcus saxobsidens [2], Blastococcus capsensis [3], Blastococcus colisei [4], Blastococcus xanthinilyticus [5], Blastococcus tunisiensis [6], and Blastococcus carthaginensis [7]), as well as desert soils and sands (with representatives such as Blastococcus aurantiacus [8], Blastococcus haudaquaticus [8], Blastococcus mobilis [8], Blastococcus atacamensis [9], and Blastococcus deserti [10]). While their ecological roles in these demanding conditions are still being unravelled, this recognition underscores their potential as valuable assets with significant biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of putative folP, folC and dfrA genes (RA086_12815, 09200 and 07270) encoding dihydropteroate synthase (EC 2.5. The detection of a putative murE gene (RA086_03955) encoding a UDP-N-acetylmuramoyl-l-alanyl-d-glutamate−2,6diaminopimelate ligase (EC 6.3.2.13) but not the UDP-N-acetylmuramoyl-l-alanyl-d-glutamate−l-lysine ligase (EC 6.3.2.7 [62]) suggested that strain WILCCON 0030 T might contain Dpm-type peptidoglycan. This was deduced from a sequence similarity analysis, which found >90 % sequence similarity between the MurE variant of strain WILCCON 0030 T (MDQ7936800) with those of the other type strains of the genus Lactiplantibacillus, including L. plantarum DSM 20174 T (KRL35199) and L. pentosus DSM 20314 T (KRK27067).…”
Section: Genome Featuresmentioning
confidence: 99%
“…While the type species, Blastococcus aggregatus , was discovered in the seawater of the Baltic Sea [1], other species were mainly isolated from monument samples, including Blastococcus saxobsidens [12], Blastococcus capsensis [13], Blastococcus colisei [14], Blastococcus xanthinilyticus [15] and Blastococcus tunisiensis [16], and from desert soils and sands, including Blastococcus aurantiacus [17], Blastococcus haudaquaticus [17], Blastococcus mobilis [17], Blastococcus atacamensis [18] and Blastococcus deserti [19]. Lastly, Blastococcus jejuensis was isolated from sand sediment of a beach [20], Blastococcus litoris from sea tidal flat sediment [21], and Blastococcus fimeti from seepage water in a landfill [17].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Blastococcus jejuensis was isolated from sand sediment of a beach [20], Blastococcus litoris from sea tidal flat sediment [21], and Blastococcus fimeti from seepage water in a landfill [17].…”
Section: Introductionmentioning
confidence: 99%